ԱՄՆ-Իրան քաղաքականության շրջափոխումը 2009-2018 թթ. - Իսկանդարյան Գոհար (YSU Journal of International Affairs, 2019)
This paper presents and analyzes the alterations in foreign policy approaches from Barack Obama administration to Donald Trump’s presidency, as well as the policies of Mahmud Ahmadinejad and Hassan Rouhani in resisting American pressures and finding the path forward. The author also evaluates the sanction mechanisms imposed by the U.S and the context around the nuclear deal. The article discusses the changes in the US regional policy, inter alia the noticeable increase in pressures on Iran during the presidency of Donald Trump, including the application of new sanctions, isolation of Iran, and encouragement of popular uprisings in the country. The alterations in the ambitions of the American administration are evident. If Democrat Barack Obama did his best to exert full control over Iranian nuclear program through sanctions and negotiations, the Republican Trump is not going to apply to negotiations and is obviously trying to influence Iran through pressures and, if possible, to topple down the regime in Tehran.